2019
DOI: 10.3390/membranes9110148
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of an Enzyme Membrane Reactor for Fructo-Oligosaccharide Production

Abstract: Fructo-oligosaccharides (FOS) are linear fructans comprising 2–5 fructose units linked to a terminal glucose residue. They are widely used as food and feed additives due to their sweetness, low calorific value, and prebiotic properties. Here we describe the synthesis of FOS catalyzed by a cell-free crude enzyme solution containing recombinant fructosyltransferase (1-FFT) produced in the yeast Kluyveromyces lactis. During the enzyme catalysis, glucose accumulates as a by-product and eventually inhibits FOS prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
1
16
1
Order By: Relevance
“…But this represents a decrease of 26.5% when both CDWs are taken into account, suggesting that both enzymes in the crude enzyme solution show transferase and hydrolysis activity. Because higher glucose concentrations can inhibit the transferase activity of the enzymes, systems such as enzyme membrane reactors may be needed for further process development so that the residence time of the enzymes can be adjusted to further optimize the transferase/hydrolysis ratio (Erdos et al, 2017;Burghardt et al, 2019b;Fan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…But this represents a decrease of 26.5% when both CDWs are taken into account, suggesting that both enzymes in the crude enzyme solution show transferase and hydrolysis activity. Because higher glucose concentrations can inhibit the transferase activity of the enzymes, systems such as enzyme membrane reactors may be needed for further process development so that the residence time of the enzymes can be adjusted to further optimize the transferase/hydrolysis ratio (Erdos et al, 2017;Burghardt et al, 2019b;Fan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In an EMBR system, this parameter is limited by membrane filtration performance, which is highly dependent on the choice of membrane and operational conditions. Our previous investigations showed that the efficiency of the EMBR system gradually declined during the long‐term production of FOS, reflecting the loss of enzyme activity due to enzyme leakage through the membrane, deactivation of the enzyme by shear stress, and the formation of sugar‐protein complexes via the Maillard reaction 16, 17. These issues were addressed in the current investigation by selecting an appropriate membrane and suitable operational conditions.…”
Section: Introductionmentioning
confidence: 91%
“…The protein composition of the feed and permeate solutions was determined by sodium dodecylsulfate polyacrylamide gel electrophoresis (SDS-PAGE) as previously described in [16].…”
Section: Protein Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The general formula is GF n and specific examples include 1-kestose (GF 2 ), nystose (GF 3 ), and 1F-fructofuranosylnystose (GF 4 ; Kovács et al, 2014 ; Ur Rehman et al, 2016 ). FOS can be obtained directly from natural sources like asparagus, garlic, chicory, onion and banana, or can be enzymatically produced from sucrose using fructosyltransferases ( Jaime et al, 2001 ; Singh et al, 2017 ; Burghardt et al, 2019a , b ). Enzymatically produced FOS are preferred by industry because the chain length can be controlled precisely by regulating the reaction conditions and duration.…”
Section: Introductionmentioning
confidence: 99%